Synthesis and In Silico Study of 5’-Chloro-2’,4-Dihydroxy-3-Methoxychalcone as Potential Inhibitors of Estrogen Receptors Alpha - Putri, Rizka Amalia; Nurramadhani, Aisyah Zahra; Islami, Agustina Amalia; Tristania, Auriel Wafiq; Aulia, Isma; Farah, Harra Ismi; Arifian, Hanggara; Rahmadani, Agung (Universitas Pendidikan Mandalika, 2025)
The high prevalence of breast cancer necessitates the discovery of new, more effective, and safer anticancer compounds. Chalcone, a flavonoid with promising anticancer activity, is limited by poor bioavailability and rare natural occurrence. In this study, a novel chalcone derivative, 5'-chloro-2',4-dihydroxy-3-methoxychalcone, was synthesized on a laboratory scale via Claisen-Schmidt condensation using 5-chloro-2-hydroxyacetophenone and 4-hydroxy-3-methoxybenzaldehyde as starting materials. The structure of the synthesized compound was confirmed by mass spectrometry and NMR analysis. Pharmacokinetic and toxicity profiles were predicted in silico using SwissADME, while molecular docking simulations with the ERα receptor were performed using AutoDockTools. The compound was obtained as a yellow solid with a yield of 70.15%, showed favorable ADME properties based on Lipinski’s and Veber’s rules, and demonstrated a binding energy of -7.82 kcal/mol to the ERα receptor, indicating potential as an anticancer agent. The novelty of this research is the successfully synthesized and characterized of this specific chalcone, which is structurally different from previously reported analogs. These findings enrich the diversity of chalcone derivatives and provide a new basis for developing synthesis-based drug candidates targeting breast cancer.